2009
DOI: 10.1038/cdd.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of tumor DNA to endothelial cells in vivo

Abstract: Tumor endothelial cells have long been regarded as genomically stable and therefore less likely to develop resistance to antiangiogenic therapies. However, recent findings have challenged this notion. We have shown that DNA can be transferred between cells through phagocytosis of apoptotic bodies by adjacent viable cells. Propagation of the ingested DNA is prevented by the activation of the p53-p21 pathway. In this study, we examined whether concomitant transfer of tumor DNA with genes that inactivate the p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…Subsequent studies have provided evidence that supports this hypothetical mechanism (11,12). Moreover, biological mechanisms of the horizontal transfer of genes from cancer cells have been described (13,14) and seem to be compatible with the hypothesis of genometastasis.…”
Section: Introductionmentioning
confidence: 57%
“…Subsequent studies have provided evidence that supports this hypothetical mechanism (11,12). Moreover, biological mechanisms of the horizontal transfer of genes from cancer cells have been described (13,14) and seem to be compatible with the hypothesis of genometastasis.…”
Section: Introductionmentioning
confidence: 57%
“…A likely source of endogenous STING ligands is tumor DNA or tumor-derived cGAMP, although it is unclear how they can spontaneously reach intracellular compartments of endothelial cells. Tumors may package DNA in apoptotic bodies and transfer it to endothelial cells (27), where it activates STING upon cGAS-mediated conversion to cGAMP (15,16). Another possibility is that tumor cGAMP is directly transferred to endothelial cells via connexin-mediated channels, as this has been previously suggested (28).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed the presence of tumor DNA in fibroblastoid cells with a frequency of 2-5% either after three weeks coculturing with apoptotic bodies or in vivo (162,163). By considering both models together, the fact that leukemia-associated translocations were detected in all MSC samples and that leukemia-specific IG gene rearrangement in only 3 of them, support the model of a common progenitor.…”
Section: Models Explaining the Presence Of Leukemia-associated Aberramentioning
confidence: 77%